Global mergers and acquisitions : combining companies across borders - Soofi, Abdol S. (Finance and financial management collection., 2014)
This book primarily deals with corporate restructuring through mergers and acquisitions (M&As). It critically examines all functions that must be performed in completing an M&A transaction. Domestic and cross-border M&A's are very similar in many respects even though differences between them also exist. To include discussions of the issues that arise in cross-border M&A transactions, the book also covers discusses such as international finance and multinational financial management.